Design and characterization of camptothecin gel for treatment of epidermoid carcinoma - Sunil T. Galatage; Aditya S. Hebalkar; Raviraj V. Gote; Omkar R. Mali; Suresh G. Killedar; Durgacharan A. Bhagwat; Vijay M. Kumbhar (SpringerOpen, 2020)
Abstract Background The objective of present research work is to design and characterize camptothecin gel using Carbopol-934 for the treatment of epidermoid carcinoma. Optimized herbal gel formulations were evaluated for homogeneity and appearance, viscosity, extrudability, spreadability, drug content, drug release, pH, and in vitro skin cancer activity on A431 cell lines. Results Mass and Infrared Spectra respectively conforms molecular weight and functional groups present in camptothecin. All the formulations F1 to F5 showed good homogeneity, pH from 6.68 to 6.90, spreadability in the range of 15.81-23.37 gm.cm/s, extrudability 85.51-90.45% w/w, drug content 89.12-96.64%, and in vitro diffusion 88.36-98.40%, respectively. The drug release study showed that all the formulations followed a diffusion-controlled, zero-order release mechanism. Anticancer activity results indicate that camptothecin gel induce cell death in A-439 cells having IC50 48.03 μg and % apoptosis 54.67 ± 4.58. Conclusion Topical delivery of camptothecin alleviates the side effects caused by systemic chemotherapy; hence, the developed herbal gel formulation can be effectively useful to deliver camptothecin in the treatment of epidermoid carcinoma on A-431 cells.